Exceptionally high whole-rock δ18O values in intra-caldera rhyolites from Northeast Iceland. (29th October 2018) - Berg, Sylvia E.; Troll, Valentin R.; Harris, Chris; Deegan, Frances M.; Riishuus, Morten S.; Burchardt, Steffi; Krumbholz, Michael
ABSTRACT: The Icelandic crust is characterized by low δ 18 O values that originate from pervasive high-temperature hydrothermal alteration by 18 O-depleted meteoric waters. Igneous rocks in Iceland with δ 18 O values significantly higher than unaltered oceanic crust ( 5.7‰) are therefore rare. Here we report on rhyolitic intra-caldera samples from a cluster of Neogene central volcanoes in Borgarfjörður Eystri, Northeast Iceland, that show whole-rock δ 18 O values between +2.9 and +17.6‰ ( n = 6), placing them among the highest δ 18 O values thus far recorded for Iceland. Extra-caldera rhyolite samples from the region, in turn, show δ 18 O whole-rock values between +3.7 and +7.8‰ ( n = 6), consistent with the range of previously reported Icelandic rhyolites. Feldspar in the intra-caldera samples ( n = 4) show δ 18 O values between +4.9 and +18.7‰, whereas pyroxene ( n = 4) shows overall low δ 18 O values of +4.0 to +4.2‰, consistent with regional rhyolite values. In combination with the evidence from mineralogy and rock H2 O contents, the high whole-rock δ 18 O values of the intra-caldera rhyolites appear to be the result of pervasive isotopic exchange during subsolidus hydrothermal alteration with 18 O-enriched water. This alteration conceivably occurred in a near-surface hot spring environment at the distal end of an intra-caldera hydrothermal system, and was probably fed by waters that had already undergone significant isotope exchange with the country rock. Alternatively, 18 O-enriched alteration fluids may have been produced during evaporation and boiling of standing water in former caldera lakes, which then interacted with the intra-caldera rock suites. Irrespective of the exact exchange processes involved, a previously unrecognized and highly localized δ 18 O-enriched rock composition exists on Iceland and thus probably within the Icelandic crust too.